A Study and Examined of Exponential Function: A Journey of Its Applications in Real Life - Sah, Kishan Kumar; Sahani, Suresh Kumar; Sahani, Kameshwar; Sah, Binod Kumar (Darul Yasin Al Sys, 2024)
In this report, we have examined the real life applications of exponential function on the following topics: depreciation, population growth, bacterial growth, compound interest, population of one-horned rhino.